STUDI BAHAN DAN KONSTRUKSI KAPAL PERIKANAN JARING INSANG DI KOTA DUMAI, PROPINSI RIAU - Jonny Zain (Berkala Perikanan Terubuk, 2010)
This research was carried out on May to August 2005 in Dumai city,which was conducted by the survey method. The research purposes are toappraising construction, type and criteria of gill-netter construction materials. Theappraisal was conducted with compare the research result on constructionguidance of Biro Klasifikasi Indonesia (BKI).Based on the research’s result were showing the generally objects of theresearch unsuitable with standard construction of wooden ship by BKI. Those areattributable the principle dimensions of the ships are not sufficient. Meanwhile,the wood types of gill-netter’s construction were used is suitable with theguidance of BKI.